2020
DOI: 10.3889/oamjms.2020.3988
|View full text |Cite
|
Sign up to set email alerts
|

Williams Flexion Exercise for Low Back Pain: A Possible Implementation in Rural Areas

Abstract: AIM: Low back pain (LBP) is a widespread complaint of all age groups. The economic burden of LBP is high, and physiotherapy has proven to reduce this. Unfortunately, physiotherapy or exercise regimen is rarely prescribed to LBP patients by doctors. Until now, there was no study regarding the application of physiotherapy exercise in Indonesia. This study aims to evaluate the effect of Williams flexion exercise (WFE) toward people with LBP. METHODS: This was a pretest-posttest experimental study design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The more the exercise frequency, the better the Oswestry Disability Index (ODI) score outcome. The implementation of this exercise was recommended among the population in the primary health-care center could be considered (25) . Both William's flexion exercises and McKenzie extension exercises were found to be efficient in reducing mechanical LBP (10) , but some study's conclusions were conflicting as to which was better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more the exercise frequency, the better the Oswestry Disability Index (ODI) score outcome. The implementation of this exercise was recommended among the population in the primary health-care center could be considered (25) . Both William's flexion exercises and McKenzie extension exercises were found to be efficient in reducing mechanical LBP (10) , but some study's conclusions were conflicting as to which was better.…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing the effectiveness of the McKenzie and William's exercise protocols for treating LBP found that the McKenzie exercise protocol was more successful at reducing LBP and speeding the recovery of pain-free range of movement in the lumbar spine in a subset of people (25) . Moldovan et al (27) early data indicated that the McKenzie exercise routine was superior than William's exercise in terms of pain reduction, pain incidence while sitting, pain-free lumbar movement, and recovery time (28) .…”
Section: Discussionmentioning
confidence: 99%
“…27 Aplikasi WFE pada LBP terbukti mengurangi derajat nyeri, meningkatkan ROM sendi-sendi punggung bawah, serta aktivitas fungsional subjek. 18,19,29 Hal ini juga terbukti pada penelitian lainnya dengan subjek para pekerja di sentra batik Papringan, Kabupaten Banyumas. 30 Berdasarkan hasil meta-analisis disimpulkan bahwa dibandingkan General Exercise (GE), CSE terbukti lebih efektif mengurangi nyeri serta memperbaiki kapasitas fungsional penderita LBP kronik dalam jangka pendek.…”
Section: Diskusiunclassified
“…Meanwhile in Thailand, the prevalence of LBP is 30%, almost the same as the global prevalence. Meanwhile in Indonesia, the prevalence of LBP among the productive age group is almost 40% (Sukmajaya et., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…William's flexion exercise, also called lumbar flexion exercise or William's exercise, was first developed by Dr. Paul William in 1937 for patients with chronic low back pain in response to his clinical observations that found that the majority of patients experiencing low back pain had degenerative vertebrae secondary to degenerative disc disease. (Sukmajaya et al, 2020). These exercises were developed for men under 50 years and women under 40 who have excessive lumbar lordosis, whose radiographs show contrast lumbar segment interarticular space.…”
Section: Introductionmentioning
confidence: 99%